Survival and human resource strategies of private higher education in facing an era of change: Insight from Indonesia - Ramaditya, Muhammad; Effendi, Syahrul; Burda, Agustian (Frontiers in Education, 2023)
Survival in private higher education can be done if universities have the superior talent to withstand the shocks of change. Hence, the human resource strategy is an essential part of surviving. Thus, this study aims to identify and determine the implementation of survival and human resource strategies in Indonesia’s private higher education is facing an era of change. The research method used is a descriptive qualitative approach. In collecting data, researchers used the archival method. The data is sourced from news, a total of 602 data sources, and obtained from online publications through trusted news and media. This study found six strategies of survival and human resource by private higher education in Indonesia to encounter an era of change: Efficiency; Quality Assurance; Customer Retention Program; Intensive Marketing Program; Opening of New Programs; Mergers, and Acquisitions. This research is expected to provide an extension of the survival and human resource strategies implemented by private universities in Indonesia in facing an era of change.